Digital Marketing Strategy to Increase Product Selling Prices - Ridzal, Nining Asniar; Sujana, I Wayan; Malik, Ernawati; Asrya, Asrya; Kirana, Laode Indra (Room of Civil Society Development, 2025)
This community service program aims to enhance the understanding and skills of MSME actors in Koholimombono Village in implementing digital marketing strategies to increase product selling prices. In the digital era, technology-based marketing plays a crucial role in expanding market reach and improving business competitiveness. However, many MSMEs still rely on conventional marketing methods due to limited knowledge and resources. The method used in this program includes seminars, hands-on training, and practical sessions covering the use of social media for marketing, cost-based and value-added pricing techniques, and product innovation to enhance market appeal. Evaluation results show that 80% of participants understood and successfully implemented digital marketing strategies in their businesses. Additionally, there was a significant increase in awareness of the importance of digitalization in marketing and improved skills in determining competitive selling prices. This program not only provides short-term benefits through increased knowledge but also involves continuous monitoring and mentoring sessions to ensure the effective implementation of digital strategies. Thus, this initiative contributes to local economic growth by enhancing MSME competitiveness.